2022
DOI: 10.1038/s41467-022-32265-5
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 antibodies and breakthrough infections in the Virus Watch cohort

Abstract: A range of studies globally demonstrate that the effectiveness of SARS-CoV-2 vaccines wane over time, but the total effect of anti-S antibody levels on risk of SARS-CoV-2 infection and whether this varies by vaccine type is not well understood. Here we show that anti-S levels peak three to four weeks following the second dose of vaccine and the geometric mean of the samples is nine fold higher for BNT162b2 than ChAdOx1. Increasing anti-S levels are associated with a reduced risk of SARS-CoV-2 infection (Hazard… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 37 publications
8
48
0
Order By: Relevance
“…Work investigating anti-spike SARS-CoV-2 antibody levels among Virus Watch participants who had received COVID-19 vaccines provided key insights into antibody waning and protection against breakthrough infections (8)(9)(10)(11). In one analysis following the vaccine rollout in the UK, we measured antibody levels in almost 9000 study participants who had received two doses of ChAdOx-S1 or BNT162b2 vaccine at 3 weeks after the second dose and 20 weeks after the second dose (9).…”
Section: What Has Been Measured?mentioning
confidence: 99%
“…Work investigating anti-spike SARS-CoV-2 antibody levels among Virus Watch participants who had received COVID-19 vaccines provided key insights into antibody waning and protection against breakthrough infections (8)(9)(10)(11). In one analysis following the vaccine rollout in the UK, we measured antibody levels in almost 9000 study participants who had received two doses of ChAdOx-S1 or BNT162b2 vaccine at 3 weeks after the second dose and 20 weeks after the second dose (9).…”
Section: What Has Been Measured?mentioning
confidence: 99%
“…Higher titres of anti-spike and anti-RBD IgG in uninfected controls compared to breakthrough cases have proved to decrease the risk of symptomatic COVID-19 mainly with Alpha (1, 4) and Delta variants (5, 7, 22). In the present study, we observed a decrease in the risk of infection as anti-RBD IgG levels increased after adjusting for immunisation regimen in the Delta period.…”
Section: Discussionmentioning
confidence: 99%
“…The median [IQR] fold reduction in neutralisation titres against the Delta isolate compared to the 19A isolate was two [1.3-2.6] for the Delta and two [1. [1][2] for the Omicron period samples, positive and negative patients combined; for the Omicron BA.1 isolate there was a median twelve-fold reduction (IQR [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]) compared to the 19A for the Delta period samples and a median eight-fold reduction (IQR [5.3-12]) for Omicron period samples (Suppl. Fig.…”
Section: Neutralisation Assaysmentioning
confidence: 99%
“…In the literature, cases of breakthrough infections have been described. They are defined as SARS-CoV-2 infection with a positive PCR test in people who are considered fully vaccinated according to the vaccine-specific schemes at the time, i.e., the single vaccination for Janssen Ad26.COV2.S and the double vaccination for the other vaccines at least 14 days previously [ 7 ]. Several studies showed that the anti-CoV2S antibody level has a positive correlation with protection against SARS-CoV-2 infection [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Aldridge et al showed, that an anti-CoV2S level ≥ 500 U/mL has a reduced risk of breakthrough infections after the second vaccination dose [ 7 ]. However, it is not clearly described in the literature which antibody level protects against severe infection or death in fully vaccinated people with subsequent SARS-CoV-2 infection with the Delta variant and whether high levels of antibodies following vaccination are predictive of an improved outcome.…”
Section: Introductionmentioning
confidence: 99%